Pengaruh Model Pembelajaran Problem-Based Learning dengan Teknik PORPE dalam Meningkatkan Kemampuan Berpikir Analitis Peserta Didik pada Mata Pelajaran Pendidikan Pancasila: Penelitian - Tanti Wulandari; Susan Fitriasari; Nisrina Nurul Insani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Education is a consciously deliberate endeavor to establish a learning environment that is inclusive and facilitates the development of learners. The main objective of this study was to understand the impact of Problem-Based Learning model with PORPE technique in cognitive capability of VII grade students at SMP Negeri 15 Bandung to understand the material in Pancasila education. The study employed a quantitative methodology which included experimental and control groups. The results showed significant variation in the teaching ability of the Problem-Based Learning model with PORPE technique compared to the group that applied the lecture-based learning approach, with the significance level in the independent samples t test posttest value of 0.021 <0.05. This indicates the effect of Problem-Based Learning model with PORPE technique in students' analytical understanding. As a result, the Problem-Based Learning model with PORPE technique is relevant to be applied in Pancasila Education lessons.